Breakfast Habits of Early Childhood Education Students: A Community-Based Poll Among PAUD Practitioners on WhatsApp - Ferdinan Sihombing; Djahra Warda Sopaliu; Linda Sari Barus; Betty Suprapti; Bani Sakti; Didik Agus Santoso (Journal of Gemilang, 2025)
Irregular breakfast habits in early childhood may adversely affect physical growth and cognitive development. This study aimed to describe breakfast patterns among early childhood education students (PAUD) based on direct observations by educators. A cross-sectional descriptive design was employed, involving 234 PAUD practitioners in West Java through a WhatsApp-based community. Data were collected using a single closed-ended question distributed to all community members and analyzed using descriptive quantitative methods. A total of 116 valid responses were obtained. Results showed that 68 participants (58.6%) reported that almost all children had breakfast every day, 45 (38.8%) stated that most children had breakfast but not daily, and 3 (2.6%) indicated that many children arrived without breakfast or had only a drink. None of the respondents reported uncertainty or a lack of observation. These findings suggest that although a majority of children maintain regular breakfast habits, a substantial proportion still demonstrate inconsistency. Community-based digital observation allowed for rapid and contextually relevant field data collection. The results may serve as a foundation for promotive and preventive interventions through nutrition literacy and healthy breakfast campaigns in PAUD settings.